CARBONATE RESERVOIR STATIC MODEL OF BATURAJA FORMATION IN PH FIELD SOUTH SUMATRA BASIN - Yudhatama, Danar
Static reservoir modeling is needed for every productive oil and gas field. It can represent 3 dimensional reservoir characteristics so that facies distribution and property reservoir will be easily understood horizontally or vertically. Static carbonate reservoir modeling of Baturaja Formation in PH field is expected to optimize the field development. The static modeling at PH field used interdisciplinary integrated data of geology, geophysics, and petrophysics. The data consisted of 7 lines of migration-class seismic and 2 check-shot data. Besides that, log data & petrophysics calculation from 9 wells, and well core from one of the well with facies description and porosity-permeability calculation are also used as main data. The method used for distribute facies data and reservoir properties is geostatistic method. Geostatistic method is a statistic technique which is used to find spatial relationship among of variable group in predicting value of the same variable at another location without data. Result of seismic interpretation showed that PH field has build-up carbonate reservoir with North-South direction. Based on the pattern from gamma rays log, there are 4 carbonate growth/precipitation cycles. Description of well core explains that there are 3 facieses, i.e. wackestone, packstone-grainstone, and coral. Each facies can be distinguished based on IGR log and PHIN-PHID. Analysis of well core and seismic section description showed that depositional environment of carbonate reservoir existed in shallow water with ramp type carbonate. The static modeling with geostatistic showed that there is similarity of pattern between facies model and property model. Validation of static model was conducted to measure the model accuracy. The validation used 2 methods, which are statistical test and blind well test. The result showed that there is similarity between original log data and modeling result. Therefore, the static reservoir model is expected represent the real subsurface condition